Hugalinis a portable and adjustable hand washing station for kids in an NGO feeding program - Dionisio, Joone Joy T.
This study focuses on the design and implementation of hugalinis, a specially designed hand washing station, with the aim of promoting regular handwashing among beneficiary children in a feeding program. The design features an adjustable height, catering to the children's varying heights, and the ability to widen, allowing it to fit into narrow spaces commonly found in feeding program venues. By encouraging and facilitating regular handwashing with the assistance of volunteers and coordinators, Hugalinis aims to create a significant impact on the children's overall health and well-being. The study recognizes the importance of hand hygiene in preventing the spread of diseases and emphasizes the potential benefits for the children's educational experience by reducing absenteeism and fostering a healthier learning environment. Through its user-friendly and accessible design, Hugalinis seeks to instill good hygiene practices and contribute to the improved health outcomes of the beneficiary children in the feeding program.